Organic electroluminescent device and display device containing heterocyclic-substituted phenanthroline compound

CN122995415APending Publication Date: 2026-10-27YANTAI XIANHUA CHEM TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510523700.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0014]本申请提供了一种有机电致发光器件和显示装置,所述有机电致发光器件包含电荷产生层,电荷产生层包含结构式如通式(Ⅰ)所示的杂环取代的菲啰啉化合物。本申请提供的有机电致发光器件,包括本申请如通式(Ⅰ)所示的杂环取代的菲啰啉化合物,该化合物作为电荷产生层材料时具有高效的电荷产生能力,能够有效提高有机电致发光器件的发光效率,降低有机电致发光器件的驱动电压并延长有机电致发光器件的使用寿命;另外,本申请如通式(Ⅰ)所示的杂环取代的菲啰啉化合物,平面刚性较强,结晶温度较高,具有良好的热稳定性,利于延长有机电致发光器件的使用寿命;使得本申请提供的有机电致发光器件具有低驱动电压、高发光效率以及较长的使用寿命。本申请提供的显示装置具有优良的显示效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995415A_ABST
    Figure CN122995415A_ABST
Patent Text Reader

Abstract

The application provides an organic electroluminescent device and display device containing a heterocyclic-substituted phenanthroline compound, which comprises a charge generation layer, and the charge generation layer comprises a heterocyclic-substituted phenanthroline compound as shown in general formula (I). The organic electroluminescent device provided by the application comprises the heterocyclic-substituted phenanthroline compound as shown in general formula (I), and the compound has high charge generation capacity when used as a charge generation layer material, can effectively improve the charge transport performance of the organic electroluminescent device, improve the luminous efficiency of the organic electroluminescent device, has a deep energy level, can be better used in combination with adjacent layer materials, thereby improving the luminous efficiency of the organic electroluminescent device, reducing the driving voltage of the organic electroluminescent device and prolonging the service life of the organic electroluminescent device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of organic light-emitting display technology, and in particular to an organic electroluminescent device and display apparatus containing a heterocyclic substituted phenanthroline compound. Background Technology

[0002] Electroluminescence (EL) refers to the phenomenon where a luminescent material emits light when excited by an electric field and subjected to current and voltage. It is a process that directly converts electrical energy into light energy. Organic electroluminescent devices (OLEDs) possess a series of advantages, including self-illumination, low-voltage DC drive, all-solid-state operation, wide viewing angle, light weight, and simple composition and manufacturing process. Compared to liquid crystal displays (LCDs), OLEDs do not require a backlight, have a wider viewing angle, lower power consumption, and a response speed up to 1000 times faster than LCDs, while their manufacturing cost is lower than that of LCDs with the same resolution. Therefore, OLEDs have a very broad application prospect.

[0003] With the continuous advancement of OLED technology in both lighting and display fields, research on high-efficiency organic materials that influence the performance of OLED devices has become increasingly focused. A high-efficiency, long-lifetime organic electroluminescent device is usually the result of an optimized combination of device structure and various organic materials. This presents both significant opportunities and challenges for chemists in designing and developing functional materials with various structures. Stacked devices can effectively improve device lifespan and have therefore become a research hotspot in recent years. Developing high-efficiency charge generation layer materials and selecting suitable light-emitting units to improve the luminous efficiency and extend the lifespan of organic electroluminescent devices has become a pressing technical problem for those skilled in the art. Summary of the Invention

[0004] The purpose of this application is to provide an organic electroluminescent device and display device containing a heterocyclic substituted phenanthroline compound, so as to improve the luminous efficiency, reduce the driving voltage, and extend the service life of the organic electroluminescent device. The specific technical solution is as follows:

[0005] A first aspect of this application provides an organic electroluminescent device comprising a charge-generating layer comprising a heterocyclic-substituted phenanthroline compound as shown in general formula (I):

[0006]

[0007] Ar is selected from unsubstituted or Rc-substituted C6-C. 30 Aryl, unsubstituted or Rc-substituted C5-C 30 Mixed aromatics;

[0008] L 1 -L2 Independently selected from chemical bonds, unsubstituted or Rc-substituted C6-C 30 aryl, unsubstituted or Rc-substituted C5-C 30 heteroaryl;

[0009] R 1 -R 2 Independently selected from hydrogen, deuterium, C1-C5 alkyl, unsubstituted or Rc-substituted C6-C 30 Aryl, unsubstituted or Rc-substituted C5-C 30 Mixed aromatics;

[0010] X 1 X 2 They are selected independently from CH or N;

[0011] The heteroatoms on the heteroaryl group or the heteroaryl group are each independently selected from O, S or N;

[0012] The Rc is independently selected from deuterium, halogen, nitro, cyano, C1-C4 alkyl, phenyl, biphenyl, terphenyl, pyridyl, pyrimidinyl, or naphthyl.

[0013] A second aspect of this application provides a display device that includes the organic electroluminescent device provided in the first aspect of this application.

[0014] This application provides an organic electroluminescent device and a display device. The organic electroluminescent device includes a charge generation layer comprising a heterocyclic-substituted phenanthroline compound with the structural formula shown in general formula (I). The organic electroluminescent device provided by this application, comprising the heterocyclic-substituted phenanthroline compound shown in general formula (I), exhibits high charge generation capability when used as a charge generation layer material. This effectively improves the luminous efficiency of the organic electroluminescent device, reduces its driving voltage, and extends its lifespan. Furthermore, the heterocyclic-substituted phenanthroline compound shown in general formula (I) has strong planar rigidity, a high crystallization temperature, and good thermal stability, which is beneficial for extending the lifespan of the organic electroluminescent device. Therefore, the organic electroluminescent device provided by this application has low driving voltage, high luminous efficiency, and a long lifespan. The display device provided by this application has excellent display performance. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these accompanying drawings.

[0016] Figure 1 This is a schematic diagram of a typical organic electroluminescent device. Detailed Implementation

[0017] The technical solutions of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.

[0018] A first aspect of this application provides an organic electroluminescent device comprising a charge-generating layer, said charge-generating layer comprising a heterocyclic-substituted phenanthroline compound as shown in general formula (I):

[0019]

[0020] Ar is selected from unsubstituted or Rc-substituted C6-C. 30 Aryl, unsubstituted or Rc-substituted C5-C 30 Mixed aromatics;

[0021] L 1 -L 2 Independently selected from chemical bonds, unsubstituted or Rc-substituted C6-C 30 aryl, unsubstituted or Rc-substituted C5-C 30 heteroaryl;

[0022] R 1 -R 2 Independently selected from hydrogen, deuterium, C1-C5 alkyl, unsubstituted or Rc-substituted C6-C 30 Aryl, unsubstituted or Rc-substituted C5-C 30 Mixed aromatics;

[0023] X 1 X 2 They are selected independently from CH or N;

[0024] The heteroatoms on the heteroaryl group or the heteroaryl group are each independently selected from O, S or N;

[0025] The Rc is independently selected from deuterium, halogen, nitro, cyano, C1-C4 alkyl, phenyl, biphenyl, terphenyl, pyridyl, pyrimidinyl, or naphthyl.

[0026] Preferably, Ar is selected from unsubstituted or Rc-substituted C6-C. 18 Aryl, unsubstituted or Rc-substituted C5-C 18 Mixed aromatics;

[0027] Preferably, L 1 -L 2 Independently selected from chemical bonds, unsubstituted or Rc-substituted C6-C 18 aryl, unsubstituted or Rc-substituted C5-C 18 heteroaryl;

[0028] Preferably, R 1 -R 2 Independently selected from hydrogen, deuterium, C1-C5 alkyl, unsubstituted or Rc-substituted C6-C 18 Aryl, unsubstituted or Rc-substituted C5-C 18 Mixed aromatic compounds.

[0029] More preferably, R 1 -R 2 The groups are independently selected from hydrogen, deuterium, methyl, ethyl, propyl, unsubstituted or Rc-substituted groups of the following compounds: benzene, biphenyl, terphenyl, naphthalene, phenanthrene, triphenylene, fluorene, fluoranthene, anthracene, dibenzofuran, dibenzothiophene, 9,9-dimethylfluorene, 9,9-diphenylfluorene, spirofluorene, pyridine, quinoline, quinazoline, pyrimidine, triazine, phenanthrene, and carbazole.

[0030] More preferably, L 1 -L 2 The subunits of the following compounds, which are chemically bonded, unsubstituted, or Rc-substituted, are selected independently from each other: benzene, pyridine, pyrimidine, quinoxaline, quinazoline, biphenyl, terphenyl, naphthalene, phenanthrene, triphenylene, fluorene, anthracene, dibenzofuran, dibenzothiophene, 9,9-dimethylfluorene, 9,9-diphenylfluorene, and spirofluorene.

[0031] More preferably, Ar is selected from the following groups of compounds that are unsubstituted or substituted by Rc: benzene, phenanthrene, naphthalene, pyridine, pyrimidine, quinoxaline, benzoxazole, dibenzofuran, quinoline, triazine, phenanthrene, and quinazoline.

[0032] In some embodiments, the heterocyclic-substituted phenanthroline compound is selected from the compounds shown in A1 to A50 below:

[0033]

[0034]

[0035]

[0036] The organic light-emitting device provided in this application includes a heterocyclic substituted phenanthroline compound as shown in general formula (I). This compound, when used as a charge-generating layer material, exhibits highly efficient charge generation capability, effectively improving the charge transport performance of the organic light-emitting device. Simultaneously, it possesses a deep energy level, allowing for better integration with adjacent layer materials, thereby improving the luminous efficiency of the organic light-emitting device, reducing its driving voltage, and extending its lifespan. Furthermore, the introduction of quinoline-substituted fragments enhances the planar rigidity of the phenanthroline compound, increases its crystallization temperature, and improves its thermal stability, further contributing to extended lifespan of the organic light-emitting device.

[0037] In this application, the groups in general formula (I) It can replace the phenanthroline ring Any hydrogen atom on it, Indicates the connection site.

[0038] In some embodiments, the charge-generating layer further includes metal Li or Yb, and the mass percentage of metal Li or Yb is 0.5%-15% based on the mass of the charge-generating layer.

[0039] In some embodiments, the thickness of the charge-generating layer is 10 nm to 30 nm.

[0040] In this application, there are no particular restrictions on the type and structure of organic electroluminescent devices. They can be organic electroluminescent devices of different types and structures known in the art, as long as at least one of the charge generation layer materials provided in this application can be used.

[0041] In some embodiments, the organic electroluminescent device includes an anode and a cathode, with m light-emitting units stacked between the anode and the cathode, and m-1 charge-generating layers between two adjacent light-emitting units. Each charge-generating layer includes an n-type charge-generating layer and a p-type charge-generating layer, where m is an integer ≥2. Each light-emitting unit includes at least one light-emitting layer, and the maximum emission wavelength of the light emitted in different light-emitting units is different. At least one of the n-type charge-generating layers includes at least one compound of formula (I) and a metal-containing material, wherein the metal-containing material includes metals, metal complexes, or combinations thereof.

[0042] In some embodiments, the light-emitting unit in the organic electroluminescent device may include a first light-emitting unit and a second light-emitting unit, which may be the same or different; a charge-generating layer may be disposed between the first light-emitting unit and the second light-emitting unit, the first light-emitting unit may be disposed between the anode and the charge-generating layer, and the second light-emitting unit may be disposed between the charge-generating layer and the cathode. The n-type charge-generating layer of the charge-generating layer may include at least one compound of formula (I) and a metal-containing material.

[0043] In some embodiments, in an organic electroluminescent device with a light-emitting unit of 2, the first light-emitting unit may further include an HT-light-emitting auxiliary layer between the light-emitting layer and the anode of the first light-emitting unit, and the first light-emitting unit includes an electron transport layer.

[0044] In some embodiments, the organic electroluminescent device of this application can be a top-emitting structure, which may include an anode, a first light-emitting unit, a charge-generating layer, a second light-emitting unit, an electron injection layer, and a transparent or semi-transparent cathode sequentially on a substrate.

[0045] The organic electroluminescent device of this application can also be a bottom-emitting device, which may include a transparent or semi-transparent anode, a first light-emitting unit, a charge generation layer, a second light-emitting unit, an electron injection layer, and a cathode sequentially on a substrate.

[0046] The organic electroluminescent device of this application can also be a light-emitting device with a dual-sided light-emitting structure, which may include, in sequence on a substrate, a transparent or semi-transparent anode, a first light-emitting unit, a charge-generating layer, a second light-emitting unit, an electron injection layer, and a transparent or semi-transparent cathode.

[0047] The first light-emitting unit includes a first hole injection layer, a first hole transport layer, a first light-emitting layer and a first electron transport layer arranged in sequence, and the second light-emitting unit includes a second hole injection layer, a second hole transport layer, a second light-emitting layer and a second electron transport layer arranged in sequence.

[0048] Furthermore, the organic electroluminescent device of this application may have an electron blocking layer between the hole transport layer and the light-emitting layer, and a hole blocking layer between the light-emitting layer and the electron transport layer. A light extraction layer may be disposed on the transparent electrode on the light-emitting side. However, the structure of the organic electroluminescent device of this application is not limited to the specific structure described above. If necessary, the above layers may be omitted or added. This application does not impose any particular limitation on the thickness of the above layers, as long as the purpose of this application can be achieved. For example, an organic electroluminescent device may sequentially comprise, on a substrate, an anode (100nm to 150nm) made of metal, a first hole injection layer (5nm to 20nm), a first hole transport layer (80nm to 140nm), an electron blocking layer (5nm to 20nm), a first light-emitting layer (15nm to 40nm), a hole blocking layer (5nm to 20nm), a first electron transport layer (10nm to 40nm), a charge generation layer (10nm to 30nm), a second hole injection layer (5nm to 20nm), a second hole transport layer (80nm to 140nm), a second light-emitting layer (15nm to 40nm), a second electron transport layer (10nm to 40nm), an electron injection layer (0.5nm to 20nm), a transparent or semi-transparent cathode (100nm to 160nm), and a light extraction layer (50nm to 90nm). Exemplarily, Figure 1 A schematic diagram of a typical organic electroluminescent device 20 is shown, in which, from bottom to top, a substrate 21, a reflective anode 22, a first hole injection layer 231, a first hole transport layer 241, a first light-emitting layer 251, a first electron transport layer 261, a charge generation layer 27, a second hole injection layer 232, a second hole transport layer 242, a second light-emitting layer 252, a second electron transport layer 262, an electron injection layer 28, and a cathode electrode 29 are sequentially arranged. It can be understood that... Figure 1 The structure of a typical organic electroluminescent device is shown only schematically. This application is not limited to this structure. The charge generation layer material of this application can be used in any type of organic electroluminescent device.

[0049] For convenience, the organic electroluminescent devices of this application are described below, but this does not imply any limitation on the scope of protection of this application. It is understood that all organic electroluminescent devices using the charge generation layer material of this application are within the scope of protection of this application.

[0050] In this application, there are no particular limitations on the substrate 21. Conventional substrates used in organic electroluminescent devices in the prior art can be used, such as glass, polymer materials, and glass and polymer materials with thin-film transistor (TFT) components.

[0051] In this application, there are no particular restrictions on the material of the reflective anode 22. It can be selected from transparent conductive materials known in the prior art such as indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO2), and zinc oxide (ZnO), or metallic materials such as silver and its alloys, aluminum and its alloys, or organic conductive materials such as poly(3,4-ethylenedioxythiophene) (PEDOT). Alternatively, the reflective anode 22 can be a multilayer structure formed from the above materials. This application does not have any particular restrictions on the number of layers in the multilayer structure. The number of layers can be selected according to actual needs, as long as it meets the purpose of this application. For example, one layer, two layers, three layers, or more layers.

[0052] In this application, there are no particular limitations on the materials of the first hole injection layer 231 and the second hole injection layer 232. They can be made of hole injection layer materials known in the art or hole transport layer materials (HTM) known in the art. For example, at least one of the known HTMs can be selected as the hole injection layer material.

[0053] In this application, the first hole injection layer 231 and the second hole injection layer 232 may each include a p-type dopant. This application does not particularly limit the type of p-type dopant, and various p-type dopants known in the art can be used. For example, the p-type dopant may be selected from, but is not limited to, at least one of the following p-1 to p-3 compounds:

[0054]

[0055] In this application, there are no particular restrictions on the amount of p-type dopant used, and the amount can be any amount known to those skilled in the art.

[0056] In this application, there are no particular restrictions on the materials of the first hole transport layer 241 and the second hole transport layer 242, and they can be made using HTM materials known in the art. This application does not specifically limit the number of hole transport layers, and the number can be adjusted according to actual needs, as long as it meets the purpose of this application; for example, one, two, three, four, or more layers.

[0057] For example, HTM for hole injection layer materials and HTM for hole transport layer materials can be selected from, but are not limited to, at least one of the following HT-1 to HT-31 compounds:

[0058]

[0059]

[0060] In this application, there are no particular restrictions on the materials of the first light-emitting layer 251 and the second light-emitting layer 252. Each of them may contain a main material for the light-emitting layer and a guest material for the light-emitting layer. There are no particular restrictions on the amount of the main material for the light-emitting layer and the guest material for the light-emitting layer. They may be amounts known to those skilled in the art.

[0061] In this application, the light-emitting layer may include a blue light-emitting layer, a green light-emitting layer, or a red light-emitting layer. There are no particular limitations on the light-emitting material in the light-emitting layer, and various light-emitting materials known to those skilled in the art can be used.

[0062] In this application, there are no particular limitations on the host material of the luminescent layer, and at least one of the luminescent layer host materials known in the art can be used. For example, at least one of the following compounds, but not limited to BH-1 to BH-10, can be used:

[0063]

[0064] In this application, there are no particular limitations on the guest material of the luminescent layer, and at least one of the luminescent layer guest materials known in the art can be used. For example, the luminescent layer guest material can be selected from, but is not limited to, at least one of the following BD-1 to BD-9 compounds:

[0065]

[0066]

[0067] In this application, there are no particular restrictions on the materials of the first electron transport layer 261 and the second electron transport layer 262, and they can be made of electron transport materials known in the art. There are no particular restrictions on the number of electron transport layers in this application, and they can be adjusted according to actual needs, as long as the purpose of this application is met; for example, one, two, three, four, or more layers.

[0068] For example, it is known that electron transport materials can be selected from, but are not limited to, at least one of the following ET-1 to ET-57 compounds:

[0069]

[0070]

[0071]

[0072] In this application, the first electron transport layer 261 and the second electron transport layer 262 may each include an n-type dopant. There is no particular limitation on the type of n-type dopant, and various n-type dopants known in the art can be used. For example, the following n-type dopant, lithium 8-hydroxyquinoline (LiQ), can be used:

[0073]

[0074] In this application, there are no particular restrictions on the amount of n-type dopant used, and the amount can be any amount known to those skilled in the art.

[0075] In this application, the charge generation layer 27 may contain at least one of the charge generation layer materials of this application, or may contain a combination of at least one of the charge generation layer materials of this application and at least one of the known charge generation layer materials.

[0076] For example, known charge-generating layer materials may be selected from, but are not limited to, at least one of the following CGL00R1 to CGL00R5 compounds:

[0077]

[0078] In this application, there are no particular restrictions on the material of the electron injection layer 28. Known electron injection layer materials in the art can be used, such as at least one of the following materials in the prior art: LiQ, LiF, NaCl, CsF, Li2O, Cs2CO3, BaO, Na, Li, Ca, etc.

[0079] In this application, there are no particular restrictions on the material of the cathode electrode 29, which can be selected from, but is not limited to, magnesium-silver mixtures, LiF / Al, ITO, Al and other metals, metal mixtures, oxides and the like.

[0080] There are no particular limitations on the method for preparing the organic electroluminescent device of this application; any method known in the art can be used. For example, this application can be prepared using the following method:

[0081] The method for fabricating organic electroluminescent devices in this application may also include, but is not limited to, the following steps:

[0082] (1) Clean the reflective anode 22 on the substrate 21 of the top-emitting organic electroluminescent device. In the cleaning machine, the anode is cleaned by chemical washing, water washing, brushing, high-pressure water washing, air knife and other steps, and then heated.

[0083] (2) Hole injection material is vacuum-deposited on the reflective anode 22 as the first hole injection layer 231;

[0084] (3) A hole transport layer material is vacuum-deposited on the first hole injection layer 231 to serve as the first hole transport layer 241;

[0085] (4) A first light-emitting layer 251 is vacuum-deposited on the first hole transport layer 241. The first light-emitting layer 251 contains a light-emitting layer host material and a light-emitting layer guest material.

[0086] (5) Vacuum evaporation of electron transport material on the first light-emitting layer 251 serves as the first electron transport layer 261;

[0087] (6) A charge generation layer material is vacuum-deposited on the first electron transport layer 261 as a charge generation layer 27;

[0088] (7) Vacuum vapor deposition of hole injection material on charge generation layer 27 as second hole injection layer 232;

[0089] (8) Vacuum evaporation of hole transport layer material on the second hole injection layer 232 serves as the second hole transport layer 242;

[0090] (9) A second light-emitting layer 252 is vacuum-deposited on the second hole transport layer 242. The second light-emitting layer 252 contains a light-emitting layer host material and a light-emitting layer guest material.

[0091] (10) Vacuum evaporation of electron transport material on the second light-emitting layer 252 serves as the second electron transport layer 262;

[0092] (11) Vacuum evaporation of electron injection material on the second electron transport layer 262 serves as electron injection layer 28;

[0093] (12) A cathode material is vacuum-deposited on the electron injection layer 28 as a cathode 29.

[0094] The above describes only a typical structure and fabrication method of an organic electroluminescent device. It should be understood that this application is not limited to this structure. The charge generation layer material of this application can be used in organic electroluminescent devices of any structure, and the organic electroluminescent device can be fabricated using any fabrication method known in the art.

[0095] A second aspect of this application provides a display device that includes the organic electroluminescent device provided in the first aspect of this application. The display device includes, but is not limited to, a monitor, a television, a tablet computer, a mobile communication terminal, etc.

[0096] There are no particular limitations on the synthesis method of the compounds in this application; any method known to those skilled in the art can be used for synthesis. The following examples illustrate the synthesis process of the compounds in this application. As used herein, room temperature refers to 25±5℃.

[0097] Synthesis example

[0098] Synthesis Example 1: Synthesis of Compound A1:

[0099]

[0100] 100 mmol of p-chlorophenylboronic acid, 100 mmol of 2-bromophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh3)4). The reaction was carried out at 80 °C for 12 h. After the reaction was completed, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M1. The amount of Pd(PPh3)4 added was 1 mol% of the p-chlorophenylboronic acid.

[0101] 100 mmol of M1, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M2. The amount of Pd(PPh3)4 added was 1 mol% of M1.

[0102] 100 mmol of 2-bromo-5-chloropyridine, 100 mmol of phenylboronic acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF), and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M3. The amount of Pd(PPh3)4 added was 1 mol% of 2-bromo-5-chloropyridine.

[0103] 100 mmol of M3, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M4. The amount of Pd(PPh3)4 added was 1 mol% of M3.

[0104] 100 mmol of M4, 100 mmol of 2-bromo-8-chloroquinoline, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M5. The amount of Pd(PPh3)4 added was 1 mol% of M4.

[0105] 100 mmol of M2, 100 mmol of M5, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, Al. The amount of Pd(PPh3)4 added was 1 mol% of M2.

[0106] 1 H NMR(400MHz,Chloroform)δ9.30(s,1H),8.80(d,J=7.2Hz,1H),8.68(d,J=7.6Hz,2H),8.48(d,J=6.8Hz,1H),8.42–8.25(m,5H),7.98(d,J=8.0 Hz,1H),7.86(d,J=7.2Hz,1H),7.74(d,J=7.2Hz,1H),7.60(d,J=7.2Hz,1H),7.55-7.32(m,7H),7.32(d,J=8.0Hz,1H),7.26((d,J=7.6Hz,2H).

[0107] Synthesis Example 2: Synthesis of Compound A3:

[0108]

[0109] 100 mmol of p-chlorophenylboronic acid, 100 mmol of 2-bromophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M1. The amount of Pd(PPh3)4 added was 1 mol% of the p-chlorophenylboronic acid.

[0110] 100 mmol of M1, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M2. The amount of Pd(PPh3)4 added was 1 mol% of M1.

[0111] 100 mmol of 2-bromo-5-chloropyridine, 100 mmol of 4-(benzoxazol-2-yl)phenylboronic acid (CAS: 1065657-51-3), 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was completed, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M3. The amount of Pd(PPh3)4 added was 1 mol% of 2-bromo-5-chloropyridine.

[0112] 100 mmol of M3, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M4. The amount of Pd(PPh3)4 added was 1 mol% of M3.

[0113] 100 mmol of M4, 100 mmol of 2-bromo-8-chloroquinoline, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M5. The amount of Pd(PPh3)4 added was 1 mol% of M4.

[0114] 100 mmol of M2, 100 mmol of M5, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder A3. The amount of Pd(PPh3)4 added was 1 mol% of M2.

[0115] 1 H NMR(400MHz,Chloroform)δ9.32(s,1H),8.80(d,J=7.2Hz,1H),8.72(d,J=7.6Hz,4H),8. 46(d,J=7.6Hz,1H),8.38(d,J=7.2Hz,2H),8.26(d,J=7.2Hz,1H),8.00(d,J=8.0Hz,1H), 7.94(d,J=7.6Hz,2H),7.86(d,J=7.2Hz,1H),7.74(t,J=6.8Hz,3H),7.64(t,J=6.8Hz,1H ),7.58(t,J=7.2Hz,3H),7.50(t,J=7.6Hz,1H),7.40-7.32(m,3H),7.24(d,J=7.6Hz,2H).

[0116] Synthesis Example 3: Synthesis of Compound A8:

[0117]

[0118] 100 mmol of 2-bromo-5-chloropyridine, 100 mmol of phenylboronic acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M1. The amount of Pd(PPh3)4 added was 1 mol% of 2-bromo-5-chloropyridine.

[0119] 100 mmol of M1, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M2. The amount of Pd(PPh3)4 added was 1 mol% of M1.

[0120] 100 mmol of M2, 100 mmol of 2,9-dichlorophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M3. The amount of Pd(PPh3)4 added was 1 mol% of M2.

[0121] 100 mmol of m-chlorophenylboronic acid, 100 mmol of M3, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M4. The amount of Pd(PPh3)4 added was 1 mol% of the amount of m-chlorophenylboronic acid.

[0122] 100 mmol of M4, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M5. The amount of Pd(PPh3)4 added was 1 mol% of M4.

[0123] 100 mmol of M2, 100 mmol of 2-bromo-8-chloroquinoline, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M6. The amount of Pd(PPh3)4 added was 1 mol% of M2.

[0124] 100 mmol of M5, 100 mmol of M6, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder A8. The amount of Pd(PPh3)4 added was 1 mol% of M5.

[0125] 1 H NMR(400MHz,Chloroform)δ9.42(s,1H),9.28(s,1H),8.42(d,J=7.2Hz,2H),8.36–8.21(m,9H),8.02(d,J=8.0Hz,2H),7.92(d ,J=7.2Hz,1H),7.80(d,J=7.2Hz,1H),7.74(t,J=7.2Hz,2H),7.68(d,J=7.6Hz,2H),7.60–7.44(m,9H),7.30(d,J=8.0Hz,1H).

[0126] Synthesis Example 4: Synthesis of Compound A9:

[0127]

[0128] 100 mmol of p-chlorobromobenzene, 100 mmol of 2-naphthylboronic acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M1. The amount of Pd(PPh3)4 added was 1 mol% of p-chlorobromobenzene.

[0129] 100 mmol of M1, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M2. The amount of Pd(PPh3)4 added was 1 mol% of M1.

[0130] 100 mmol of M2, 100 mmol of 2,9-dichlorophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M3. The amount of Pd(PPh3)4 added was 1 mol% of M2.

[0131] 100 mmol of m-chlorophenylboronic acid, 100 mmol of M3, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M4. The amount of Pd(PPh3)4 added was 1 mol% of the amount of m-chlorophenylboronic acid.

[0132] 100 mmol of M4, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M5. The amount of Pd(PPh3)4 added was 1 mol% of M4.

[0133] 100 mmol of 2-bromo-5-chloropyridine, 100 mmol of phenylboronic acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M6. The amount of Pd(PPh3)4 added was 1 mol% of 2-bromo-5-chloropyridine.

[0134] 100 mmol of M6, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M7. The amount of Pd(PPh3)4 added was 1 mol% of M6.

[0135] 100 mmol of M7, 100 mmol of 2-bromo-8-chloroquinoline, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M8. The amount of Pd(PPh3)4 added was 1 mol% of M7.

[0136] 100 mmol of M5, 100 mmol of M8, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder A9. The amount of Pd(PPh3)4 added was 1 mol% of M5.

[0137] 1H NMR(400MHz,Chloroform)δ9.28(s,1H),8.70(d,J=7.2Hz,2H),8.42–8.30(m,7H),8.26(d,J=7.2Hz,1H),8.12–7.96( m,4H),7.88(d,J=7.2Hz,1H),7.82(d,J=7.6Hz,2H),7.76–7.45(m,13H),7.34(d,J=7.2Hz,1H),7.26(d,J=7.6Hz,2H).

[0138] Synthesis Example 5: Synthesis of Compound A26:

[0139]

[0140] 100 mmol of p-chlorophenylboronic acid, 100 mmol of 4-chloro-2,9-dimethyl-1,10-phenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M1. The amount of Pd(PPh3)4 added was 1 mol% of the p-chlorophenylboronic acid.

[0141] 100 mmol of M1, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M2. The amount of Pd(PPh3)4 added was 1 mol% of M1.

[0142] 100 mmol of 2-bromo-5-chloropyridine, 100 mmol of 1-naphthoic acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M3. The amount of Pd(PPh3)4 added was 1 mol% of 2-bromo-5-chloropyridine.

[0143] 100 mmol of M3, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M4. The amount of Pd(PPh3)4 added was 1 mol% of M3.

[0144] 100 mmol of M4, 100 mmol of 2-bromo-8-chloroquinoline, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M5. The amount of Pd(PPh3)4 added was 1 mol% of M4.

[0145] 100 mmol of M2, 100 mmol of M5, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, A26. The amount of Pd(PPh3)4 added was 1 mol% of M2.

[0146] 1 H NMR(400MHz,Chloroform)δ9.30(s,1H),8.96(d,J=7.2Hz,1H),8.38(d,J=7.2Hz,1H),8.28(d, J=7.2Hz,1H),8.20(d,J=7.2Hz,1H),8.06(d,J=7.2Hz,1H),7.94(t,J=7.2Hz,2H),7.86(d,J=6. 8Hz,1H),7.80(d,J=7.2Hz,1H),7.76(d,J=7.2Hz,1H),7.72(d,J=7.6Hz,1H),7.64(d,J=7.2Hz, 1H),7.58–7.42(m,6H),7.34(d,J=7.6Hz,1H),7.22(d,J=7.6Hz,4H),2.76(s,3H),2.69(s,3H).

[0147] Synthesis Example 6: Synthesis of Compound A34:

[0148]

[0149] 100 mmol of m-chlorophenylboronic acid, 100 mmol of 2-bromophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M1. The amount of Pd(PPh3)4 added was 1 mol% of the amount of m-chlorophenylboronic acid.

[0150] 100 mmol of M1, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M2. The amount of Pd(PPh3)4 added was 1 mol% of M1.

[0151] 200 mmol of M2, 100 mmol of 2-bromo-8-chloroquinoline, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 2 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, A34. The amount of Pd(PPh3)4 added was 2 mol% of M2.

[0152] 1 H NMR(400MHz,Chloroform)δ8.95(s,1H),8.80(d,J=7.2Hz,2H),8.65(s,1H),8.44(d,J=7.2Hz,4H),8.32(d,J=7.2Hz,2H),8.24 (d,J=7.6Hz,2H),7.88(d,J=7.6Hz,2H),7.80(d,J=6.8Hz,1H),7.70–7.48(m,9H),7.34(d,J=8.0Hz,2H),7.20(d,J=8.0Hz,1H).

[0153] Synthesis Example 7: Synthesis of Compound A39:

[0154]

[0155] 100 mmol of m-chlorophenylboronic acid, 100 mmol of 2-bromophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M1. The amount of Pd(PPh3)4 added was 1 mol% of the amount of m-chlorophenylboronic acid.

[0156] 100 mmol of M1, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M2. The amount of Pd(PPh3)4 added was 1 mol% of M1.

[0157] 100 mmol of 2,4-diphenyl-6-[3-(4,4,5,5-tetramethyl-1,3,2-dioxacyclopentaborane-2-yl)phenyl]-1,3,5-triazine (CAS: 1269508-31-7), 100 mmol of 2-bromo-8-chloroquinoline, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was completed, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M3. The amount of Pd(PPh3)4 added was 1 mol of 2,4-diphenyl-6-[3-(4,4,5,5-tetramethyl-1,3,2-dioxacyclopentaborane-2-yl)phenyl]-1,3,5-triazine.

[0158] 100 mmol of M2, 100 mmol of M3, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, A39. The amount of Pd(PPh3)4 added was 1 mol% of M2.

[0159] 1H NMR (400MHz, Chloroform) δ8.80(d,J=7.2Hz,1H),8.67(s,1H),8.55(s,1H),8.46(d,J=7.6Hz,2H),8.40–8.25(m,8H),7.88(d ,J=7.6Hz,1H),7.80(d,J=7.2Hz,1H),7.72(d,J=7.2Hz,1H),7.68–7.46(m,12H),7.34(d,J=8.0Hz,1H),7.22(d,J=8.0Hz,1H).

[0160] Synthesis Example 8: Synthesis of Compound A46:

[0161]

[0162] 100 mmol of phenylboronic acid, 100 mmol of 2,9-dichlorophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M1. The amount of Pd(PPh3)4 added was 1 mol% of the amount of phenylboronic acid.

[0163] 100 mmol of m-chlorophenylboronic acid, 100 mmol of M1, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M2. The amount of Pd(PPh3)4 added was 1 mol% of the amount of m-chlorophenylboronic acid.

[0164] 100 mmol of M2, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M3. The amount of Pd(PPh3)4 added was 1 mol% of M2.

[0165] 100 mmol of 2-bromo-5-chloropyridine, 100 mmol of dibenzofuran-4-boric acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M4. The amount of Pd(PPh3)4 added was 1 mol% of 2-bromo-5-chloropyridine.

[0166] 100 mmol of M4, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M5. The amount of Pd(PPh3)4 added was 1 mol% of M4.

[0167] 100 mmol of M5, 100 mmol of 2-bromo-8-chloroquinoline, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M6. The amount of Pd(PPh3)4 added was 1 mol% of M5.

[0168] 100 mmol of M3, 100 mmol of M6, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, A46. The amount of Pd(PPh3)4 added was 1 mol% of M3.

[0169] 1H NMR(400MHz,Chloroform)δ9.31(s,1H),8.45–8.32(m,7H),8.26(d,J=7.6Hz,1H),8.16(d,J=7.2Hz,1H),8.08 (d,J=7.2Hz,1H),8.02(d,J=7.6Hz,1H),7.98(d,J=7.2Hz,1H),7.86(d,J=7.1Hz,1H),7.72–7.50(m,9H),7.40 -7.32(m,7H).

[0170] Synthesis Example 9: Synthesis of Compound A48:

[0171]

[0172] 100 mmol of p-chlorobromobenzene, 100 mmol of pyridine-3-boric acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder M1. The amount of Pd(PPh3)4 added was 1 mol% of p-chlorobromobenzene.

[0173] 100 mmol of M1, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M2. The amount of Pd(PPh3)4 added was 1 mol% of M1.

[0174] 100 mmol of M2, 100 mmol of 2,9-dichlorophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M3. The amount of Pd(PPh3)4 added was 1 mol% of M2.

[0175] 100 mmol of m-chlorophenylboronic acid, 100 mmol of M3, 41.4 g of potassium carbonate (300 mmol), 800 mL of toluene, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 80 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M4. The amount of Pd(PPh3)4 added was 1 mol% of the amount of m-chlorophenylboronic acid.

[0176] 100 mmol of M4, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M5. The amount of Pd(PPh3)4 added was 1 mol% of M4.

[0177] 100 mmol of 2,3-dichloroquinoxaline, 100 mmol of phenylboronic acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M6. The amount of Pd(PPh3)4 added was 1 mol% of 2,3-dichloroquinoxaline.

[0178] 100 mmol of M6, 100 mmol of 4-chlorophenylboronic acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M7. The amount of Pd(PPh3)4 added was 1 mol% of M6.

[0179] 100 mmol of M7, 100 mmol of pinacol diborate, 41.4 g of potassium carbonate (300 mmol), and 800 mL of dioxane were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 100 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M8. The amount of Pd(PPh3)4 added was 1 mol% of M7.

[0180] 100 mmol of M8, 100 mmol of 2-bromo-8-chloroquinoline, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, M9. The amount of Pd(PPh3)4 added was 1 mol% of M8.

[0181] 100 mmol of M5, 100 mmol of M9, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF, and 200 mL of water were added to a reaction flask, along with 1 mol% of Pd(PPh3)4. The reaction was carried out at 60 °C for 12 h. After the reaction was complete, the reaction was stopped, and the reactants were cooled to room temperature. Water was added, the mixture was filtered, washed with water, and the resulting solid was purified by recrystallization from toluene to obtain a white powder, A48. The amount of Pd(PPh3)4 added was 1 mol% of M5.

[0182] 1 H NMR(400MHz,Chloroform)δ9.24(s,1H),8.86(d,J=7.6Hz,2H),8.75–8.67(m,5H),8.58(s,1H),8.52(d,J=6.8Hz,1H),8.42(d,J=7.2 Hz,2H),8.34(d,J=7.2Hz,2H),8.06(d,J=7.6Hz,2H),7.90(d,J=7.2Hz,1H),7.86–7.75(m,3H),7.70–7.45(m,9H),7.38-7.20(m,7H).

[0183] Other compounds in this application can be synthesized by selecting suitable starting materials according to the above synthetic examples, or by selecting any other suitable method and starting materials.

[0184] Example 1

[0185] A glass substrate coated with a 150nm thick ITO transparent conductive layer was ultrasonically treated in a commercial cleaning agent, rinsed in deionized water, ultrasonically degreased in an acetone-ethanol mixed solvent, baked in a clean environment until all moisture was removed, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam to obtain a glass substrate with an anode.

[0186] Then, the glass substrate with the anode was placed in a vacuum chamber and evacuated to a vacuum level of less than 10. -5 A first hole injection layer is vacuum-deposited on the anolyte film of the aforementioned glass substrate with an anode. The material of the first hole injection layer includes hole injection layer material HT-3 and p-type dopant p-1. The deposition is performed using a multi-source co-evaporation method. The deposition rate of hole injection layer material HT-3 is adjusted to 0.1 nm / s, and the deposition rate of p-type dopant p-1 is 3% of the deposition rate of hole injection layer material HT-3. The total film thickness is 10 nm. The hole injection layer material HT-3 and p-type dopant p-1 are as follows:

[0187]

[0188] Then, HT-3 hole transport layer material is vacuum-deposited on the first hole injection layer as the first hole transport layer, wherein the deposition rate is 0.1 nm / s and the deposition film thickness is 80 nm.

[0189] Then, a first light-emitting layer is vacuum-deposited on the first hole transport layer. The first light-emitting layer includes a host material BH-5 and a guest material BD-4. The deposition is performed using a multi-source co-evaporation method. The deposition rate of the host material BH-5 is adjusted to 0.1 nm / s, and the deposition rate of the guest material BD-4 is 3% of the deposition rate of the host material BH-5. The total film thickness is 30 nm. The host material BH-5 and the guest material BD-4 are as follows:

[0190]

[0191] Then, a first electron transport layer is vacuum-deposited on top of the first light-emitting layer. The materials of the first electron transport layer are electron transport material ET30 and n-type dopant LiQ. The deposition rate of electron transport material ET30 is 0.1 nm / s, the deposition rate ratio of electron transport material ET30 to n-type dopant LiQ is 7:3, and the total film thickness is 30 nm. The electron transport material ET30 and n-type dopant LiQ are as follows:

[0192]

[0193] The first hole injection layer, the first hole transport layer, the first light-emitting layer, and the first electron transport layer together constitute the first light-emitting unit;

[0194] On the uppermost first electron transport layer of the first light-emitting unit, compound A1 and ytterbium (Yb) provided in this application are deposited as a charge generation layer, wherein the deposition rate of compound A1 is 0.01 nm / s, the deposition rate ratio of compound A1 to Yb is 98:2, and the total deposition film thickness is 10 nm.

[0195] A second hole injection layer is deposited on top of the charge generation layer. The material of the second hole injection layer includes hole injection layer material HT-3 and p-type dopant p-1. The evaporation rate of hole injection layer material HT-3 is adjusted to 0.1 nm / s, the ratio of the evaporation rates of hole injection layer material HT-3 and p-type dopant p-1 is 97:3, and the total evaporation film thickness is 10 nm.

[0196] Then, HT-3 hole transport layer material is vacuum-deposited on the second hole injection layer as the second hole transport layer, wherein the deposition rate is 0.1 nm / s and the deposition film thickness is 80 nm.

[0197] Then, a second light-emitting layer is vacuum-deposited on the second hole transport layer. The second light-emitting layer includes a host material BH-5 and a guest material BD-4. The deposition is performed using a multi-source co-evaporation method. The deposition rate of the host material BH-5 is adjusted to 0.1 nm / s, the deposition rate of the guest material BD-4 is 3% of the deposition rate of the host material BH-5, and the total deposition thickness is 30 nm.

[0198] Then, a second electron transport layer is vacuum-deposited on the second light-emitting layer. The electron transport layer material is electron transport material ET30 and n-type dopant LiQ. The deposition rate of electron transport material ET30 is 0.1 nm / s, the deposition rate ratio of electron transport material ET30 to n-type dopant LiQ is 7:3, and the total deposition film thickness is 30 nm.

[0199] The second hole injection layer, the second hole transport layer, the second light-emitting layer, and the second electron transport layer together constitute the second light-emitting unit;

[0200] Then, a 0.5 nm thick LiF layer is vacuum-deposited on the uppermost second electron transport layer of the second light-emitting unit as an electron injection layer, wherein the deposition rate is 0.1 nm / s;

[0201] Finally, an Al layer with a thickness of 150 nm was vacuum-deposited on the electron injection layer as the cathode electrode of the organic electroluminescent device, wherein the deposition rate was 0.1 nm / s.

[0202] Examples 2 to 9

[0203] Except for replacing A1 with A3, A8, A9, A26, A34, A39, A46, and A48 respectively, the rest is the same as in Example 1. See Table 1 for details.

[0204] Example 10

[0205] Except for adjusting the evaporation rate ratio of compound A9 to Yb to 88:12, everything else is the same as in Example 4.

[0206] Comparative Example 1

[0207] Except for the use of CGL00R1 instead of A1 as the charge generation layer material, everything else is the same as in Example 1; CGL00R1 is as follows:

[0208]

[0209] Comparative Example 2

[0210] Except for replacing A1 with CGL-R as the charge generation layer material, everything else is the same as in Example 1; CGL-R is as follows:

[0211]

[0212] Comparative Example 3

[0213] Except for replacing A1 with CGL-R' as the charge generation layer material, everything else is the same as in Example 1; CGL-R' is as follows:

[0214]

[0215] Comparative Example 4

[0216] Except for the use of CGL-R' instead of A9 as the charge generation layer material, everything else is the same as in Example 10.

[0217] The organic electroluminescent devices prepared by the above process were subjected to the following performance measurements:

[0218] Under the same brightness, the driving voltage, current efficiency, and lifetime of the organic electroluminescent devices prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were measured using a digital source meter and a luminance meter. Specifically, the voltage was increased at a rate of 0.1V per second, and the measurement was performed when the brightness of the organic electroluminescent device reached 1000 cd / m². 2 The voltage at that time is the driving voltage, and the current density at that time is measured simultaneously; the ratio of brightness to current density is the current efficiency; the life test of LT95 is as follows: using a luminance meter at 1000 cd / m² 2 At a constant current, the brightness of the organic electroluminescent device decreased to 950 cd / m² under the specified brightness. 2The time is expressed in hours. The results are shown in Table 1.

[0219] Table 1 Performance results of organic electroluminescent devices

[0220]

[0221] As shown in Table 1, the organic electroluminescent devices in Examples 1-10, which use the heterocyclic substituted phenanthroline compounds provided in this application as the charge generation layer material, exhibit lower driving voltage, higher current efficiency, and longer LT95 lifetime compared to those in Comparative Examples 1-4, which use known materials in the prior art as the charge generation layer material. This demonstrates that when the heterocyclic substituted phenanthroline compounds as shown in general formula (I) are used as the charge generation layer material in organic electroluminescent devices, the driving voltage can be effectively reduced, current efficiency improved, and device lifespan extended. Furthermore, the heterocyclic substituted phenanthroline compounds of this application can significantly improve the luminous efficiency and extend the lifespan of organic electroluminescent devices, thereby obtaining high-performance organic electroluminescent devices.

[0222] The above description is merely a preferred embodiment of this application and is not intended to limit the scope of protection of this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application are included within the scope of protection of this application.

Claims

1. An organic electroluminescent device comprising a charge-generating layer, said charge-generating layer comprising a heterocyclic-substituted phenanthroline compound as shown in general formula (I): in, Ar is selected from C6-C, either unsubstituted or substituted by Rc. 30 Aryl, unsubstituted or Rc-substituted C5-C 30 Mixed aromatics; L 1 -L 2 Independently selected from chemical bonds, unsubstituted or Rc-substituted C6-C 30 aryl, unsubstituted or Rc-substituted C5-C 30 heteroaryl; R 1 -R 2 Independently selected from hydrogen, deuterium, C1-C5 alkyl, unsubstituted or Rc-substituted C6-C 30 Aryl, unsubstituted or Rc-substituted C5-C 30 Mixed aromatics; X 1 X 2 They are selected independently from CH or N; The heteroatoms on the heteroaryl group or the heteroalkylene group are each independently selected from O, S or N; The Rc is independently selected from deuterium, halogen, nitro, cyano, C1-C4 alkyl, phenyl, biphenyl, terphenyl, pyridyl, pyrimidinyl, or naphthyl.

2. The organic electroluminescent device according to claim 1, wherein, Ar is selected from C6-C, either unsubstituted or substituted by Rc. 18 Aryl, unsubstituted or Rc-substituted C5-C 18 Mixed aromatics; L 1 -L 2 Independently selected from chemical bonds, unsubstituted or Rc-substituted C6-C 18 aryl, unsubstituted or Rc-substituted C5-C 18 heteroaryl; R 1 -R 2 Independently selected from hydrogen, deuterium, C1-C5 alkyl, unsubstituted or Rc-substituted C6-C 18 Aryl, unsubstituted or Rc-substituted C5-C 18 Mixed aromatic compounds.

3. The organic electroluminescent device according to claim 1, wherein, The R 1 -R 2 The groups are independently selected from hydrogen, deuterium, methyl, ethyl, propyl, unsubstituted or Rc-substituted groups of the following compounds: benzene, biphenyl, terphenyl, naphthalene, phenanthrene, triphenylene, fluorene, fluoranthene, anthracene, dibenzofuran, dibenzothiophene, 9,9-dimethylfluorene, 9,9-diphenylfluorene, spirofluorene, pyridine, quinoline, quinazoline, pyrimidine, triazine, phenanthrene, and carbazole.

4. The organic electroluminescent device according to claim 1, wherein, The L 1 -L 2 The subunits of the following compounds, which are chemically bonded, unsubstituted, or Rc-substituted, are selected independently from each other: benzene, pyridine, pyrimidine, quinoxaline, quinazoline, biphenyl, terphenyl, naphthalene, phenanthrene, triphenylene, fluorene, anthracene, dibenzofuran, dibenzothiophene, 9,9-dimethylfluorene, 9,9-diphenylfluorene, and spirofluorene.

5. The organic electroluminescent device according to claim 1, wherein, The Ar is selected from the following groups of compounds that are unsubstituted or substituted by Rc: benzene, phenanthrene, naphthalene, pyridine, pyrimidine, quinoxaline, benzoxazole, dibenzofuran, quinoline, triazine, phenanthrene, and quinazoline.

6. The organic electroluminescent device according to claim 1, wherein, The heterocyclic-substituted phenanthroline compounds are selected from the compounds shown in A1 to A50 below:

7. The organic electroluminescent device according to claim 1, wherein, The charge-generating layer further includes metal Li or Yb, and the mass percentage of metal Li or Yb is 0.5%-15% based on the mass of the charge-generating layer.

8. The organic electroluminescent device according to any one of claims 1-7, wherein, The thickness of the charge generation layer is 10nm-30nm.

9. A display device comprising the organic electroluminescent device according to any one of claims 1-8.